Flexible, conductive, and anisotropic thermoplastic polyurethane/polydopamine /MXene foam for piezoresistive sensors and motion monitoring - Chen, Qiang; Gao, Qingsen; Wang, Xin; Schubert, Dirk W.; Liu, Xianhu (Composites Part A-Applied Science and Manufacturing, 2022)
It is a challenge to manufacture pressure sensing materials with flexibility, high sensitivity, wide detection range for the development of intelligent electronic products. Herein, a pressure sensor based on thermoplastic polyurethane (TPU)/polydopamine (PDA)/MXene conductive composite foam (TPMF) was prepared by a combination of directional freezing and dip-coating methods. The compressive strength of anisotropic TPU foam (TF) in the vertical direction is increased by 48.1% compared with isotropic foam. Besides, the conductive foam (0.25 S/m) with an MXene content of 3.45 wt% exhibits low density (105.5 mg/cm3), high porosity (91.2%) and good resistance response behavior. The sensor based on TPMF exhibits excellent flexibility, fast response times (∼40 ms), and good durability over 5000 cycles. Furthermore, the composite foam has excellent recognition ability for different compressive strain amplitudes (up to 80%) and a wide stress range (10 Pa-122.5 kPa), as well as a high gauge factor (GF) up to 2.36 in the strain range of 2.5%-20%. The sensor has shown application potential in many fields, including voice recognition, health monitoring, motion monitoring, and artificial electronic skin.
CRIS-Team Scopus Importer:2022-01-28
Keywords: A. Foam; B. Anisotropy; B. Electrical properties; Sensor